Carbon taxes crowd out climate concern: Experimental evidence from sustainable consumer choices - Alice Pizzo; Christina Gravert; Jan M. Bauer; Lucia A. Reisch (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We examine the impact of a carbon tax on consumer choices via a large-scale online randomized controlled trial. Higher taxes generally reduce the demand for high-carbon goods. Compared to an import tax, a carbon tax reduces demand when the tax is zero (i.e., announced but not levied) but shows relatively higher demand for high-carbon goods when a positive tax is introduced. This contradiction of basic price theory is entirely driven by climate-concerned consumers. Our findings suggest that carbon taxes can crowd out climate concerns, leading to important implications for policy.
Keywords: Q58; C90; D03; D90; Q50; Q51; 330; Behavioral response; Carbon pricing; Climate change; Experiment; Moral licensing